EFFECTIVENESS OF GROUP COUNSELING SERVICES WITH A MUHASABAH APPROACH IN REDUCING STUDENTS ACADEMIC PROCRASTINATION AT SMA NEGERI 1 LINTAU BUO - Hariyati; Ardimen; Silvianetri (Prodi Bimbingan dan Konseling, Fakultas Keguruan dan Ilmu Pendidikan, UKI, Jakarta, 2021)
The background of this research was most of students at SMA Negeri 1 Lintau Buo postponed their academic assignments even though counselors had done many efforts in counseling but the result was not significant. Therefore, it needed a new approach to overcome those problems. This research aims to investigate the effectiveness of group counseling services with a muhasabah approach to reduce students academic procrastination at SMA Negeri 1 Lintau Buo in 2020/2021 academic year. The design of this research was quasi-experimental with one group pretest and posttest design. The population of this research was the eleventh grade students of SMA N 1 Lintau Buo in 2020/2021 academic year. The samples were chosen by simple random sampling. The sample was XI IPS 4. Then, 20 students were divided into 2 groups; 10 students as the experimental class and 10 students as the control class. The instruments used to get the data were questionnaire of procrastination. T-test independent sample and N-Gain analysis were used to analyze the data. The results of the research showed that the students academic procrastination decreased after implementing muhasabah approach, but this approach is not effective to reduce students academic procrastination significantly based on N-Gain analysis. In conclusion, the muhasabah approach is effective in reducing students academic procrastination. The results of the research showed that the students academic procrastination decreased after implementing muhasabah approach, but this approach is not effective to reduce students academic procrastination significantly based on N-Gain analysis. In conclusion, the muhasabah approach is effective in reducing students academic procrastination. The results of the research showed that the students academic procrastination decreased after implementing muhasabah approach, but this approach is not effective to reduce students academic procrastination significantly based on N-Gain analysis. In conclusion, the muhasabah approach is effective in reducing students academic procrastination.